Suburban crossroads : the fight for local control of immigration policy - Vicino, Thomas J. (Lexington Books, 2013)
"The political debate over comprehensive immigration reform in the United States reached a pinnacle in 2006. When Congress failed to implement federal immigration reform, this spurred numerous local and state governments to confront immigration policy in their own jurisdictions. In fear of becoming sanctuaries for immigrants, numerous local communities confronted and implemented their own policies to limit immigration. Thomas J. Vicino unravels the political debate behind local ordinances such as the controversial Illegal Immigration Relief Act and similar laws. He examines the evolution of the struggle for local control in three cities and suburbs--beginning in Carpentersville, Illinois, then in Farmer's Branch, Texas, and ending in Hazleton, Pennsylvania. Drawing on numerous interviews, census data analysis, and field visits, Thomas J. Vicino carefully explains how and why the definition of local neighborhood problems determined the policy outcomes. These provocative findings offer new perspectives on the local and state immigration debate as well as new reflections on future directions in policy and planning for local communities."--Publisher's website